Manifestações neurológicas da infeção por influenza em adolescente - Catarina Neto Viveiros; Ana Luisa Correia; Raquel Rocha; Ana Paula Aguiar; Marco Pereira (Sociedade Brasileira de Pediatria, 2022)
OBJECTIVE: Neurological complications connected to influenza are rare. We report a case of a 17-year-old teenager with fever and neurological manifestations. CASE REPORT: 17-year-old teenager with altered mental status and seizures. Imaging investigation and cerebrospinal fluid analysis did not show relevant alterations. The nasopharyngeal swab was positive for influenza B virus. We assumed a possible case of influenza B encephalitis. COMMENTS: Encephalitis associated with influenza infection should be considered when respiratory symptoms and altered mental status are present, if the epidemiological context is appropriate. In influenza encephalopathy, viral invasion of the central nervous system is usually not found and imaging investigation is often normal, constituting a diagnostic challenge.